2011
DOI: 10.1016/s1413-8670(11)70245-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk of coronary artery disease in individuals infected with human immunodeficiency virus

Abstract: There is a high prevalence of risk factors for CAD in the studied population, with dyslipidemia being the most frequent. HDL-cholesterol and triglycerides were the most frequently altered factors and were associated with the use of protease inhibitors. Risk assessed by the FRS was low in most cases. CACS > 0 was found in 32.5%, demonstrating the need to re-evaluate the strategies for assessing cardiovascular risk in the HIV-infected population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The finding that PI-based ART was associated with a faster decline in TG levels, and a slower increase in TC and HDL-C levels, compared to NNRTI-based ART, was not surprising as individuals may have been switched over to lipid-friendly PIs. When the percentage change in lipid levels over time was considered, the findings that the PIs were associated with higher TG and moderately higher TC levels were consistent with results from other studies [24][25][26]. The risk of excess dyslipidaemia due to ART depended on the specific PI used, as was observed in this and other studies [27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…The finding that PI-based ART was associated with a faster decline in TG levels, and a slower increase in TC and HDL-C levels, compared to NNRTI-based ART, was not surprising as individuals may have been switched over to lipid-friendly PIs. When the percentage change in lipid levels over time was considered, the findings that the PIs were associated with higher TG and moderately higher TC levels were consistent with results from other studies [24][25][26]. The risk of excess dyslipidaemia due to ART depended on the specific PI used, as was observed in this and other studies [27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the evidence levels, the following distribution was observed: four on level IV (10,16,20,23) ; three on level V (21)(22)24) ; and ten on level VI (11)(12)(13)(14)(15)(16)(17)(18)(19)(25)(26) .…”
Section: Resultsmentioning
confidence: 97%
“…The characterization of the 17 articles showed the year of publication varied between 2001 and 2016, with six articles published in Brazil (10)(11)(12)(13)(14)(15) , five in the United States (16)(17)(18)(19)(20) , four in European countries (21)(22)(23)(24) , one article in Cameroon (25) and one in Chile (26) . Regarding the evidence levels, the following distribution was observed: four on level IV (10,16,20,23) ; three on level V (21)(22)24) ; and ten on level VI (11)(12)(13)(14)(15)(16)(17)(18)(19)(25)(26) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is increasing use of nonlipid-based assessments of CVD risk, such as estimation of endothelial function (flow-mediated vasodilatation or C-IMT) and coronary artery calcification by coronary CT, which have been shown to predict CVD events in the general population, particularly Dyslipidemia, atherosclerosis & cardiovascular disease in an aging population living with HIV Review future science group in older individuals [100][101][102], their use in HIVpositive populations has largely been confined to research. However, some studies have suggested that use of C-IMT or coronary artery calcification estimation identifies subclinical atherosclerosis more accurately than the use of the more traditional risk assessments in HIV-positive subjects [103,104]. Whether their use in HIV-positive patients assessed at moderate CVD risk using conventional risk assessment may better identify those with significant atherosclerotic burden who require interventions remains to be seen.…”
Section: Assessment and Management Of Cvd Risk In Hivmentioning
confidence: 99%